A Simple Flow Injection Sensing System for the Real-Time On-Line Determination of Chemical Oxygen Demand Based on 3D Au-NPs/TiO2 Nanotube Arrays - Si, Hewei; Zhang, Xidong; Lin, Shiwei (Frontiers in Materials, 2019)
3D TiO2 nanotube arrays loaded with Au nanoparticles (3D Au-NPs/TNTAs) were prepared to effectively enhance the photoelectrocatalytic properties. A simple flow injection sensing system was proposed for the real-time on-line determination of chemical oxygen demand using the 3D Au-NPs/TNTAs electrode. The proposed photoelectrochemical oxidative degradation principle of the sensing system was analyzed and validated by the representative organic compounds with known COD values at a potential bias 1.5 V under UV illumination. A practical detection limit of the sensing system is 0.18 mg/L and the linear range is 1.92 - 3360 mg/L under the optimum conditions. In the experimental process, the sensing system exhibits good long-term stability and reproducibility.